2020
DOI: 10.1111/jdv.16098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of cutaneous squamous cell carcinoma: perspective for treatment strategies

Abstract: Cutaneous squamous cell carcinoma (cSCC) represents 20% of all skin cancers. Although primary cSCCs can be successfully treated with surgery, a subset of highly aggressive lesions may progress to advanced disease, representing a public healthcare problem with significant cancer-related morbidity and mortality. A complex network of genes (TP53, CDKN2A, NOTCH1 and NOTCH2, EGFR and TERT) and molecular pathways (RAS/RAF/MEK/ERK and PI3K/AKT/mTOR) have been shown to play an important role in the pathogenesis of cSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 110 publications
0
23
0
1
Order By: Relevance
“…The inactivation of p53 in cSCC is mainly due to gene mutations or interactions with viral proteins such as HPV E6 [66] (Figure 6a). Missense "hot spots" mutations are mainly characterized by UV-signature (i.e., C > T or CC > TT transitions), which enable keratinocytes to prevent apoptosis and to promote clonal expansion of TP53 mutated cells [66]. The role of p53 in UV-B-induced carcinogenesis has been confirmed in animal models [67].…”
Section: Cell Cycle Regulation Apoptosis and Senescence Tp53mentioning
confidence: 99%
See 1 more Smart Citation
“…The inactivation of p53 in cSCC is mainly due to gene mutations or interactions with viral proteins such as HPV E6 [66] (Figure 6a). Missense "hot spots" mutations are mainly characterized by UV-signature (i.e., C > T or CC > TT transitions), which enable keratinocytes to prevent apoptosis and to promote clonal expansion of TP53 mutated cells [66]. The role of p53 in UV-B-induced carcinogenesis has been confirmed in animal models [67].…”
Section: Cell Cycle Regulation Apoptosis and Senescence Tp53mentioning
confidence: 99%
“…Several feedback loops regulate this kinase cascade [65]. ERK act on multiple cytosolic and nuclear targets, including kinases, cytoskeletal protein, and transcription factors [66] (Figure 6C). For instance, ERK regulates the transcriptional activity of ETS1 that, in turn, promotes transcription of several key players of tumor development and progression, including genes involved in cellular proliferation and survival (bcl-2, caspase-1, p16INK4a, p21, p53) and extracellular matrix remodeling and angiogenesis (metalloproteases) [30].…”
Section: Ras-raf-mek-erk Pathwaymentioning
confidence: 99%
“… 27 Moreover, the PI3K/AKT/mTOR pathway was displayed by Nardo et al to play an indispensable role in the pathogenesis of CSCC. 14 A recent study indicated that miR-21 directly targets and inhibits the expression of PTEN (a negative modulator of the PI3K/AKT pathway), and miR-21 inhibition upregulated PTEN expression but impaired the PI3K/AKT pathway, thereby elevating liver cancer cell apoptosis. 28 Furthermore, miR-21 down-regulation causes an impairment in PI3K/AKT pathway activation in Burkitt’s lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway has been evidenced to be involved in the pathogenesis of CSCC. 14 Notably, another study has proved that the PI3K/AKT serves as a mediator in CSCC cell growth and development. 15 On top of that, the combined interplay of miR-21, TIMP3 and PI3K/AKT pathway in CSCC is lack of explorations.…”
Section: Introductionmentioning
confidence: 99%
“…Die Therapiemöglichkeiten des PEK haben sich kürzlich durch die Immuntherapie deutlich verbessert [16,17]. Weil PEKeinesehrhoheMutationslastaufweisen, wird auch ein gutes Ansprechen auf PD-1/PD-L1-Inhibitoren erwartet [18,19].…”
Section: Therapieunclassified